Magma recharge and mush rejuvenation drive paroxysmal activity at Stromboli volcano - Chiara Maria Petrone; Silvio Mollo; Ralf Gertisser; Yannick Buret; Piergiorgio Scarlato; Elisabetta Del Bello; Daniele Andronico; Ben Ellis; Alessio Pontesilli; Gianfilippo De Astis; Pier Paolo Giacomoni; Massimo Coltorti; et al. (Nature Communications, 2022)
Petrological studies along with volcano monitoring data relate the unusual 2019 explosive activity at Stromboli volcano (Italy) to deep magma recharges up to a few days prior the eruption and a direct link between deep and shallow magma reservoirs.